Multilayer multiconfiguration time-dependent Hartree method: implementation and applications to a Henon-Heiles Hamiltonian and to pyrazine - Vendrell, Oriol; Meyer, Hans-Dieter (The journal of chemical physics, 2011)
The multilayer multiconfiguration time-dependent Hartree (ML-MCTDH) method is discussed and a fully general implementation for any number of layers based on the recursive ML-MCTDH algorithm given by Manthe [J. Chem. Phys. 128, 164116 (2008)] is presented. The method is applied first to a generalized Henon-Heiles (HH) Hamiltonian. For 6D HH the overhead of ML-MCTDH makes the method slower than MCTDH, but for 18D HH ML-MCTDH starts to be competitive. We report as well 1458D simulations of the HH Hamiltonian using a seven-layer scheme. The photoabsorption spectrum of pyrazine computed with the 24D Hamiltonian of Raab et al. [J. Chem. Phys. 110, 936 (1999)] provides a realistic molecular test case for the method. Quick and small ML-MCTDH calculations needing a fraction of the time and resources of reference MCTDH calculations provide already spectra with all the correct features. Accepting slightly larger deviations, the calculation can be accelerated to take only 7 min. When pushing the method toward convergence, results of similar quality than the best available MCTDH benchmark, which is based on a wavepacket with - 4.6× - 10 - 7 - 4.6×107 - time-dependent coefficients, are obtained with a much more compact wavefunction consisting of only - 4.5× - 10 - 5 - 4.5×105 - coefficients and requiring a shorter computation time.
Gesehen am 07.12.2022